Semantic web technologies for ubiquitous computing resource management in smart spaces. (9th July 2007) - Soldatos, John; Stamatis, Kostas; Azodolmolky, Siamak; Pandis, Ippokratis; , Lazaros Polymenakos
Context-aware ubiquitous computing environments tend to be highly distributed and heterogeneous, while also featuring increased dynamism as elements, devices and middleware components join, leave and change their status. In such environments, information is derived and fused with numerous sensors and context-aware middleware components. As a result, directory and naming services, along with reasoning mechanisms, are at the heart of any non-trivial ubiquitous computing application. In this paper, we argue that semantic web technologies can deal with directory service requirements of ubiquitous computing environments, much more efficiently than the wide range of legacy mechanisms. To justify this claim, we introduce a model that could greatly facilitate the development, deployment and management of ubiquitous computing applications. This model relies on semantic web technologies (i.e., ontology management) and facilitates the integration of hardware and middleware elements in the scope of a ubiquitous computing application. Using this model and its underlying ontology management schemes, we implemented proof-of-concept applications in the scope of a smart space comprising numerous sensors, actuators and middleware components. Based on the implementation experience, we outline the merits of using semantic web technologies in ubiquitous context-aware computing and smart spaces.